Growing pains : building sustainably successful organizations - Flamholtz, Eric G.; Randle, Yvonne (John Wiley & Sons, Inc., 2016)
An insightful and practical toolkit for managing organizational growth Growing Pains is the definitive guide to the life cycle of an organization, and the optimization strategies that make the organization stronger. Whether growth is rapid, slow, or not occurring at all, this book provides a host of solid tools and recommendations for putting everything in order. Now in its fifth edition, this invaluable guide has been fully updated to reflect the current economic climate, and includes new case studies and chapters discussing nonprofit life cycle tools, leadership challenges and the "leadership molecule", and real-world applications of the frameworks presented. The latest empirical research is presented in the context of these ideas, including new data on strategic organizational development. Mini-cases that illustrate growth management issues have been added throughout, with additional coverage of international entrepreneurship and companies that provide a frame of reference for the perspective being developed. Growing pains are normal, and a valuable indicator of organizational health, but they indicate the need for new systems, processes, and structure to support the organization's size. This book provides a practical framework for managing the process, applicable to organizations of all sizes. Understand the key stages of growth and the challenges of each Measure your organization's growing pains and development Deploy new tools that facilitate positive organizational development Make the necessary transitions required to ensure sustainable success Some companies, even after brilliant beginnings, lose their way as growth throws them for a loop. Growing Pains identifies the underlying factors that promote long term success, and gives you a framework for successfully managing the transitions of growth